(untitled) (Filološke studije, 2019)
The article shows the problems and possibilities of intercultural discourse on the example of two foreign born writers, Florjan Lipuš and Feridun Zaimoglu, within a German speaking context. As both of them initially applied literature as a means of protest against their respective hegemonic societies the role of subversion poses itself. It is possible to see how in one case, Zaimoglu, subversion gave way to acceptance, whereas in the second case, Lipuš, the author stagnated in his selfimposed role of the rebellious outsider. Marginality thus became a constituent part of dominant culture. One can see here that acceptance is not only a requirement from the majority, but that it can also be fruitful from a minority perspective.